High-time-resolution chemical composition and source apportionment of PM2.5 in northern Chinese cities: implications for policy - Y. Zhang; Y. Zhang; Y. Zhang; J. Tian; J. Tian; J. Tian; Q. Wang; Q. Wang; Q. Wang; Q. Wang; L. Qi; M. I. Manousakas; et al. (Atmospheric Chemistry and Physics, 2023)
Fine particulate matter (PM2.5) pollution is still one of China's most important environmental issues, especially in northern cities during wintertime. In this study, intensive real-time measurement campaigns were conducted in Xi'an, Shijiazhuang, and Beijing to investigate the chemical characteristics and source contributions of PM2.5 and explore the formation of heavy pollution for policy implications. The chemical compositions of PM2.5 in the three cities were all dominated by organic aerosol (OA) and nitrate (NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="a6a4c5911a740e8377438efb607d4b86"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-9455-2023-ie00001.svg" width="9pt" height="16pt" src="acp-23-9455-2023-ie00001.png"/></svg:svg>). Results of source apportionment analyzed by a hybrid environmental receptor model (HERM) showed that the secondary formation source contributed more to PM2.5 compared to other primary sources. Biomass burning was the dominant primary source in the three pilot cities. The contribution of coal combustion to PM2.5 is non-negligible in Xi'an and Shijiazhuang but is no longer an important contributor in the capital city of Beijing due to the execution of a strict coal-banning policy. The potential formation mechanisms of secondary aerosol in the three cities were further explored by establishing the correlations between the secondary formation sources and aerosol liquid water content (ALWC) and Ox (O3+NO2), respectively. The results showed that photochemical oxidation and aqueous-phase reaction were two important pathways of secondary aerosol formation. According to source variations, air pollution events that occurred in campaigns were classified into three types: biomass-combustion-dominated, secondary-formation-source-dominated, and a combination of primary and secondary sources. Additionally, this study compares the changes in chemical composition and source contributions of PM2.5 in past decades. The results suggest that the clean-energy replacements for rural households should be urgently encouraged to reduce the primary source emissions in northern China, and collaborative control on ozone and particulate matter needs to be continuously promoted to weaken the atmosphere oxidation capacity for the sake of reducing secondary aerosol formation.